Enhancing fuel burning efficiency by regulate spark plug voltage supply - Mohd Ariffin, Maslina (2013)
Nowadays, fuel consumption, fuel efficiency and fuel economy is number one priority for people. The need to reduce fuel consumption is because oil reserves are running low and the cost of gasoline will only increase day by day. The benefits of increased fuel economy is significant energy, cost saving, reducing greenhouse emission, improved air quality and etc. To increase the fuel efficiency, many fuel efficient vehicles was created. Fuel-efficient vehicles are extremely important because we need to cut our fuel consumption and find other way of powering cars. Thus, this research introduced the system that can reduce fuel consumption and improve car performance when the car battery voltage is increase. This system use ac power supply replacing the car battery to get the dc power supply. Also, the system enables to increase voltage from 12 volt to 16 volt supplied to spark plug to enhance fuel burning efficiency. Aims of project are to improve car performance and reduce fuel consumption. To meet the desired aim of this research, the experiment to measure car performance using power performance that are produce from current voltage and the experiment similarly concept with combustion process was done. From that experiment, the system had improved car performance and lessing fuel consumption to 33% when the voltage increases to 16V.